Tea culture and industry: Customer tea buying decision‐making power shaped by social capital in the presence of mutual trust. Issue 1 (8th April 2020) - Khan, Tariq H.; Yuzhen, Duan; Ali, Sumran; Ariyesti, Fitri R.
Abstract : This study contributes to the literature on tea culture and industry by examining the impact of social capital on customer perception which controls the decision to buy the tea products. Prior research suggests that individual cognition is the most essential element to target to achieve the required tea purchasing decision power. Individuals who socially connect and share views via social media are more likely to share a buy recommendation that psychologically inspires the buying decisions of customers. For present study data were collected through a structured questionnaire from 300 universities students usually use social media to get required information, knowledge and ask from other friends regarding product recommendation which is more trustworthy and easily accessible. The findings of the present study provide new insights into the development of the tea industry and encourage the use of tea products.